ANALISIS DAYA SAING EKSPOR KOMODITAS KARET ALAM PROVINSI JAWA TENGAH - Ismiati Marfuah Rochmat; Darsono Darsono; Erlyna Wida Riptanti (Universitas Sebelas Maret, 2017)
This research aims to determine how the competitiveness of natural rubber export of Central Java Province in terms of its comparative advantages and competitive advantages. The basic method of research is analytical descriptive. The research location is Central Java Province, where the area is potentially in manages natural rubber to make the superior plantation commodities and has been exported continuously. The data used in this research are primary and secondary data. The data analysis used is XCI (Export Competitiveness Index) and RCA (Revealed Comparative Advantage) analysis. The results show: The competitiveness of natural rubber export of Central Java Province observed from the competitive advantage by using XCI (Export Competitiveness index) analysis, shows that the average XCI value of natural rubber Central Java Province during 2001 until 2015 is more than one that is 1,08 and indicates that the natural rubber commodity of Central Java Province has an increasing competitive trend in the international market. The competitiveness of natural rubber export of Central Java Province observed from comparative advantage by using RCA (Revealed Comparative Advantage) analysis shows that the average value of RCA of natural rubber of Central Java Province during 2001 to 2015 is more than one that is 6,82 and indicates that natural rubber commodities have a high comparative advantage (above the world average).